GAYA PENGURUSAN KONFLIK ANTARA PENGURUS-SUBORDINAT MENURUT PERSPEKTIF ISLAM: KAJIAN EMPIRIKAL DI PUSAT KEWANGAN LUAR PESISIR ANTARABANGSA - Muhammad, Mohd Zulkifli; Japang, Minah; Ibrahim, Mohd Faisol (Jurnal Syariah, 2010)
This article is a case study which related to conflict management style in International Offshore Financial Centre organizational setting. Generally, the study carried out among 62 staffs consisting of both managerial positions-subordinates relationships. An interesting finding prevailed that both managers and subordinates agreed that prudent conflict management style could bring forward an endeavor yet practical benefit in boosting generating new ideas and innovative interpersonal development among staffs. However, uncontrollable and inefficient conflict management on the other hand, significantly could be a hindering factor of productivity flow and thus, issued an emotional disturbance among managers-subordinates relationship which then cause unconstructive work culture. Despite discussing issues on impact of conflict in organization, the study indeed focusing and proposing on the Islamic perspective in conflict resolution. Therefore the article discussed some major conflict settlement style based on Rahim’s Organizational Conflict Inventory-II (ROCI-II) with slightly modification on Islamic work ethics adapted from Quran and Hadith.